Analysis Determinants of Postpartum Maternal Mortality at Sidoarjo Regency in 2012 - Rahmawati, Puspita; Martini, Santi; Wahjuni, Chatarina Umbul (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTThe maternal mortality ratio (MMR) in Indonesia remains high, i.e approximately 359 per 100.000 life birth (IDHS 2012). MMR is an indicator of motherâs health, especially the risk of being death for a mother while pregnant and delivery. Mostly the majority of maternal mortality (MMR) is occurring in the first two days after delivery and care after giving birth services required to manage complication. Sidoarjo regency has high postpartum maternal mortality case, so it is necessary to study determinants influencing postpartum maternal mortality in that regency. This research aimed to analyze the determinants that influence postpartum maternal mortality. This research was an observational research using case control study. Number of samples was 21 cases and 43 controls. Data were analyzed by univariate analysis, bivariate analysis with chi-square test, and multivariate analysis with multiple logistic regressions. The result showed that the determinants which influence postpartum maternal mortality according to multivariate analysis were pre-eclampsia/eclampsia (OR = 20,98; 95%CI : 2,250 â 323,416; p = 0,008) and delivery complication (OR = 5,47; 95%CI : 1,356 â 22,022; p = 0,017). Probability of mother to have risk of postpartum maternal mortality with all those risk factors above was 92,9%. This research recommended are need to detect early sign of pregnancy, delivery, and post delivery complication, especially danger sign of pre-eclampsia/eclampsia, referral preparation, and pregnancy planning.Â Keywords :Â  postpartum maternal mortality, determinants, pre- Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  eclampsia/eclampsia, delivery complication.